Qualidade em jornalismo : avaliação dos instrumentos de transparência e media accountability na gestão editorial das TVs legislativas do Brasil - Pereira, Ana Rachel Gonçalves (2022)
The research evaluates the adherence scale of practices of transparency and media accountability in journalism practiced by brazilian states and federal legislative TVs. The data was gathered and analysed through a software, Q-Avalia, developed by Federal University of Sergipe’s researchers, which is still in a trial phase and, therefore, subject to improvement, but it enables the evaluation of journalistic quality through a protocol with pre-established indicators. For this purpose, the existence, content and accessibility level of transparency instruments and media accountability were analyzed from television news produced by legislative TVs, which have journalistic programs complementary to the parliament sessions broadcasts. As a result, it will be made available a ranking of broadcasters with their respective levels of performance regarding their level of editorial quality, measured according to the level of adherence to the transparency indicators and media accountability implemented by each of them.